La relación entre el gobierno corporativo y la valoración, apalancamiento y desempe\~no financiero en Colombia; The relationship between corporate governance, valuation, leverage and financial performance in Colombia - Luis Ángel Meneses Cerón; Jaime Andrés Carabalí Mosquera; Camilo Andrés Pérez Pacheco (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– Financial literature and empirical evidence in global markets indicate that those companies that adequately manage their stakeholders, strengthen and disclose their corporate governance policies, achieve greater effectiveness in their institutional operation. In the context of an emerging market, this article studies the relationship between the quality of corporate governance practices and the valuation, leverage and financial performance of Colombian companies during the period 2008-2018. Based on the theory of resource and agency dependency, predictions are established about the relationships between the variables of interest. Companies listed on the Colombian Stock Exchange were examined and a Bloomberg index was used to measure the quality of corporate governance practices. Regression models were used on an unbalanced data panel including time and company fixed effects. The results indicate that there is a positive relationship between the corporate governance index and the financial performance and valuation measures of companies, and a negative relationship with the total leverage measure. These results reveal that good corporate governance practices lead to better functioning within companies, which is reflected in a better performance in the market over time.
Keywords: G10; GQ5; G30; G34; 330; corporate governance; valuation; financial leverage; corporate performance; COLCAP